2013
DOI: 10.1068/b38045
|View full text |Cite
|
Sign up to set email alerts
|

Urban Form and the Environmental Impact of Commuting in a Segregated City, Santiago de Chile

Abstract: The literature on the relationship between the built environment and travel has identified population density and the mix of land uses as key characteristics of the urban form that affect travel patterns. However, in cities with strong sociospatial disparities it is not clear if these characteristics apply in the same way. In this paper we use regression analysis to estimate the influence of the spatial growth pattern of Santiago, Chile, on the environmental impact of commuting. Our findings can be summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…At the metropolitan scale, containing the spread of the built-up area and promoting infill development could reduce the environmental impact of commuting. On a previous work we showed that, like in other cities, in Santiago also densification favors a more environmental friendly transportation pattern because of the wider use of mass transportation [49]. However, in dense areas trips are also longer due to the peripheral location and the traffic congestion, although the overall environmental impact is lower because the wider use of public transport offsets the negative impact of longer trips.…”
Section: Implications For Accessibility and Travelmentioning
confidence: 69%
See 2 more Smart Citations
“…At the metropolitan scale, containing the spread of the built-up area and promoting infill development could reduce the environmental impact of commuting. On a previous work we showed that, like in other cities, in Santiago also densification favors a more environmental friendly transportation pattern because of the wider use of mass transportation [49]. However, in dense areas trips are also longer due to the peripheral location and the traffic congestion, although the overall environmental impact is lower because the wider use of public transport offsets the negative impact of longer trips.…”
Section: Implications For Accessibility and Travelmentioning
confidence: 69%
“…On the one hand, although income dominates the household vehicle ownership decision, some built environment characteristics also have an influence, such as dwelling unit density, local land use mix, street layout, distance to CBD and proximity to Metro [48]. On the other, the modal choice, the time spent travelling, and the environmental impact are also affected by the urban form and the spatial organization of the city [49]. Despite the urban outgrowth that is gradually transforming the city into a metropolitan region with several employment nodes, Santiago today remains, to a large extent, monocentric.…”
Section: Implications For Accessibility and Travelmentioning
confidence: 99%
See 1 more Smart Citation
“…Veneri (2010) posited that in Italy, the colocation effects are long term and thus are undermined by the short-term rigidity in residential mobility (p. 405). Empirical studies in Latin America and Asia also lend no support to the colocation hypothesis: suburbanization increases commute (Gainza and Livert 2013), lengthens the average travel time (Jun 2012), and increases household vehicular travel distance (Burapatana and Ross 2007). A comparative study found that employment suburbanization results in lower excess commuting in Los Angeles, United States, than in Seoul, South Korea (Jun et al 2018), confirming the observed contrasting results between the United States and other countries.…”
Section: Urban Structure–travel Relationship In Other Countriesmentioning
confidence: 99%
“…Many recent researches have explored the characteristics of urban forms via an integration of spatial and semantics criteria for many application domains. Amongst several relevant examples, let us mention the analysis of urban climate (Eeftens et al, 2013;Futcher et al, 2013), disaster management (Liu, Luan, & Zhong, 2012), energy consumption (Chena et al, 2011) and transportation studies (Gainza & Livert, 2013;Rybarczyk & Wu, 2014). A comprehensive review of these researches shows that the morphological criteria range significantly from first order to more intricate derived measures such as landscape metrics (Fan & Myint, 2014;Herold, Couclelis, & Clarke, 2005), densities and spatial distributions (Edussuriya, Chan, & Yec, 2011;Filicaia, 2007), sky views and open spaces (Eeftens et al, 2013), and accessibility and connectivity measures (Contreras, Blaschke, Kienberger, & Zeil, 2013;Eeftens et al, 2013).…”
Section: Research Backgroundmentioning
confidence: 99%